2009
DOI: 10.1007/978-90-481-2259-2_19
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines and GABA-GABAA Receptor System in the Cat Carotid Body

Abstract: Benzodiazepines (BZs) suppress ventilation possibly by augmenting the GABA(A) receptor activity in the respiratory control system, but precise sites of action are not well understood. The goals of this study were: (1) to identify GABA(A) receptor subunits in the carotid body (CB) and petrosal ganglion (PG); (2) to test if BZs exert their effects through the GABA(A) receptor in the CB chemosensory unit. Tissues were taken from euthanized adult cats. RNA was extracted from the brain, and cDNA sequences of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…For example, GABA A receptors have been shown to be located in murine gut [21], in cat carotid body [22], in rat taste bud [23], in human thyroid [24], human hepatocellular [25], human peripheral blood mononuclear cells [26], and human prostate [27]. GABA B receptors have been reported in spider leg mechanosensilla [28], rat testis and sperm [29], the rat olfactory bulb [30], the rat taste bud [23], the rat gastrointestinal tract [31], and rat cardiomyocytes [32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, GABA A receptors have been shown to be located in murine gut [21], in cat carotid body [22], in rat taste bud [23], in human thyroid [24], human hepatocellular [25], human peripheral blood mononuclear cells [26], and human prostate [27]. GABA B receptors have been reported in spider leg mechanosensilla [28], rat testis and sperm [29], the rat olfactory bulb [30], the rat taste bud [23], the rat gastrointestinal tract [31], and rat cardiomyocytes [32].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the effects of midazolam are specific to its ability to potentiate GABA (Asl et al, 2008;Igarashi et al, 2009) and are not the result of generalized CNS depression. We also Values are expressed as mean±SD found that icv midazolam decreased artery blood pressure produced by icv ropivacaine, and that increasing anesthetic depth with isoflurane significantly decreased the artery blood pressure produced by icv ropivacaine in the animals, which indicated that the decrease in artery blood pressure was not simply the result of icv midazolam.…”
Section: Discussionmentioning
confidence: 90%
“…In the setting of cocaine abuse, the clinical and magnetic resonance imaging features can be confused with other complications of cocaine abuse and high-risk lifestyles. [2][3][4] …”
mentioning
confidence: 99%
“…Since then, one article has raised the possibility of multifocal inflammatory leukoencephalopathy resulting from levamisole-adulterated cocaine, suggesting that this complication can also occur with small amounts of levamisole found in cocaine. 4 We encourage health care professionals to add leukoencephalopathy to the growing list of complications resulting from this adulterant frequently detected in illicit drugs. Though newer benzodiazepine controlled substances are marketed as "nonbenzodiazepines," zolpidem activates identical benzodiazepine sleep modulation ␥-aminobutyric acid type A receptors as classic benzodiazepines, 2 enhancing superficial stage 1/2 sleep interval at the expense of restorative rapid eye movement and stage 3/4 deep slow wave sleep (SWS).…”
mentioning
confidence: 99%
See 1 more Smart Citation